Transversal dose profile reconstruction for clinical proton beams: A detectors inter-comparison. (February 2020) - Catalano, R.; Petringa, G.; Cuttone, G.; Bonanno, V.P.; Chiappara, D.; Musumeci, M.S.; Puglia, S.M.R.; Stella, G.; Scifoni, E.; Tommasino, F.; Cirrone, G.A.P.
Highlights: The device shows promising qualities as control system for 2-D relative dosimetry thanks to its characteristics. Experimental results demonstrate that the accuracy of the system is very close to the existing dosimetric devices. At 100 MeV proton energy, the agreement between our system and the EBT3 is within 6% for all the investigated parameters. The use of the device can be obviously extended to other ion beams, where the lateral penumbras are expected to be sharper. Abstract: Purpose: The main purpose of this work is the inter-comparison between different devices devoted to the transversal dose profile recostruction for daily QA tests in proton therapy. Methods: The results obtained with the EBT3 radiochromic films, used as a reference, and other common quality control devices, have been compared with those obtained with a beam profiling system developed at the "Laboratori Nazionali del Sud" of Italian Institute for Nuclear Physics (INFN-LNS, Catania, Italy). It consists of a plastic scintillator screen (thickness 1 mm), mounted perpendicularly to the beam axis and coupled with a highly sensitive CCD detector in a light-tight box. Results and conclusion: The tests, carried out both at the INFN-LNS and Trento Proton Therapy Center facilities, show, in general, a good agreement between the different detectors. The beam profiling system, in particular, appears to be a promising quality control device for 2-D relative dosimetry, because of its linear response in a dose rate range useful for proton therapy treatments, its high spatial resolution and its short acquisition and processing time.